BICKERSTAFF BRAINSTEM ENCEPHALITIS AND MILLER FISHER SYNDROME – VARIANT OF GUILLAIN-BARRÉ SYNDROME A SPECTRUM OF CLINICAL MANIFESTATION OF SAME DISEASE - KULSHRESTHA, MANISH; KULSHRESTHA, ANJALI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Guillain-Barré syndrome (GBS) and its variants are parainfectious (2/3 cases) neurological illness involving the lower motor neuron but they can also involve central nervous system (CNS). Bickerstaff brainstem encephalitis (BBE) and Miller Fisher syndrome (MFS) are the two variants of GBS with CNS involvement. The present case series highlights the variable presentation and laboratory findings in BBE and MFS, which may help clinicians in early recognition and timely management of the condition.